Genetic susceptibility to mycobacteria and other infectious pathogens in humans. - Bellamy, R; Hill, A (1998)
Substantial evidence exists that host genes are important in determining the outcome of infection with mycobacteria and other intracellular pathogens. Geographical variation in the prevalence of malaria has facilitated the recognition of many genes important in determining interindividual variability in susceptibility to the severe forms of this infection. This success has, however, been difficult to achieve in other infectious diseases. Recently a variety of study designs including large-scale association-based population case/control studies of candidate genes, family-based linkage studies, investigation of rare individuals with exceptional mycobacterial susceptibility and comparison with mouse models of disease has enabled identification of host genes which contribute to susceptibility to mycobacterial disease. This work demonstrates that a large number of genes are probably important in susceptibility to mycobacterial pathogens and provides a model for the investigation of genetic susceptibility to other infectious diseases.